Pan-cancer analysis of ADAMs: A promising biomarker for prognosis and response to chemotherapy and immunotherapy - Ma, Bo; Yu, Riyue (Frontiers in Genetics, 2023)
Background: Members of ADAM family has been found to play a great important role in cancers. However, comprehensive analysis of the landscape of ADAM family in pan-cancer has not been studied. Methods: we evaluated the expression level and prognostic value of ADAMs in pan-cancer cohort, based on the latest public databases, and investigated the relationship between ADAMs with tumor microenvironment (TME), Stemness score, immune subtype, chemotherapy related drug sensitivity and immunotherapy outcome in pan-cancer Results : ADAMs was differently expressed between tumor and para-carcinoma tissues in pan-cancer, and the expression of ADAMs were significantly correlated with patients prognosis. Furthermore, ADAMs were significantly correlated with stromal score and immune score based on the TME analysis. Then we found they were also correlated with RNAss and DNAss in TCGA pan-cancer cohort. By investigating the CellMiner database, our results indicated ADAMs were strikingly correlated with the sensitivity of various drugs including Raloxifene, Tamoxifen and so on. In IMvigor210 and GSE78220 cohorts, we found that ADAMs were also correlated with immunotherapy response and immune activation genes. Moreover, qPCR was utilized to detect differential expression of ADAM9 in cancer and para-carcinoma tissues in our cohorts. Conclusion : These results indicated the role of ADAMs in cancer progression and it provides ideas for further exploring ADAMs as potential pan-cancer targets..